2022
DOI: 10.1111/jce.15505
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of electrophysiology procedures in patients with obstruction of the inferior vena cava

Abstract: Aims The objective of the study was to conduct a systematic review to describe and compare the different approaches for performing cardiac electrophysiology (EP) procedures in patients with interrupted inferior vena cava (IVC) or equivalent entities causing IVC obstruction. Methods We conducted a structured search to identify manuscripts reporting EP procedures with interrupted IVC or IVC obstruction of any aetiology published up until August 2020. No restrictions were applied in the search strategy. We also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Obtaining adequate transseptal assess is essential to perform a left‐sided ablation. The same systemic review reported that the superior approach from SVC was the most frequently used strategy (52%), followed by inferior approach via the azygos or hemiazygos vein (24%), transhepatic approach (14%), and retroaortic approach (10%) 5 . In our patient, childhood surgical ASD repair surgery further complicated the transseptal attempts.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Obtaining adequate transseptal assess is essential to perform a left‐sided ablation. The same systemic review reported that the superior approach from SVC was the most frequently used strategy (52%), followed by inferior approach via the azygos or hemiazygos vein (24%), transhepatic approach (14%), and retroaortic approach (10%) 5 . In our patient, childhood surgical ASD repair surgery further complicated the transseptal attempts.…”
Section: Discussionmentioning
confidence: 77%
“…The same systemic review reported that the superior approach from SVC was the most frequently used strategy (52%), followed by inferior approach via the azygos or hemiazygos vein (24%), transhepatic approach (14%), and retroaortic approach (10%). 5 In our patient, childhood surgical ASD repair surgery further complicated the transseptal attempts. The superior approach from the LIJ vein was our choice with TEE guidance (esophageal posterior location with relatively standard views) instead of ICE (left-sided Azygous position visualizing dextrocardic chambers).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…4 , 5 , 6 , 7 , 8 , 9 It is important for proceduralists to be aware that in such instances, less-than-favorable alternatives including superior (SVC and brachial) and transhepatic approaches should also be anticipated. 10 , 11 Superior approaches via the SVC and basilic veins have successfully been used in such instances and are preferred by many experienced operators. However, in the setting of a transfemoral approach, the utilization of longer sheaths allows for better navigation and maneuverability of the catheters.…”
Section: Discussionmentioning
confidence: 99%